EFEKTIVITAS KOMUNIKASI DALAM PELAKSANAAN KEGIATAN PENGUATAN LEMBAGA DISTRIBUSI PANGAN MASYARAKAT (Kasus Gapoktan Maju Bersama Desa Bumiharjo Kecamatan Batanghari Kabupaten Lampung Timur) - M. Fikri Akbar (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2014)
Government Regulation No. 68 of 2002 on food security stated that food needs fulfillment is not only the matter of production, but also distribution issues, which cause many problems. The objectives of the research were to describe a strengthening program of food community distribution, institutional (P-PLDPM), analyze forms of communication of Joint Farmer’s Groups (Gapoktan) in the program and analyze communication effectiveness of in the program. The research was designed as a descriptive and correlational survey research. The study site selection was purposively selected, namely Gapoktan Maju Bersama of Bumiharjo Village, Batanghari Subdistrict, East Lampung District. Primary data collection and field observations were carried out during April to June 2012. Respondents of this study amounted to 83 farmers who know the P-PLDPM. The data used in this research consisted of primary data and secondary data. Data analysis applied descriptive statistics and Spearman Rank Correlation Analysis using Excel and SPSS 15.0 program for Windows. Gapoktan Maju Bersama have been implementing the strengthening community food distribution institutional program since 2010 up to date. The most frequent communication forms, which were performed by Gapoktan Maju Bersama management was a group meeting with the field companion and farmer members. In the group meeting, a discussion always takes place. Farmers' level of understanding of the P-PLDPM activities determined the communication effectiveness, because it could significantly change knowledge and behavior levels.